Investigation of the energy spectra and the electron–hole alignment of the InAs/GaAs quantum dots with an ultrathin cap layer. (August 2016) - Gorshkov, Alexey P.; Volkova, Natalia S.; Istomin, Leonid A.; Zdoroveishev, Anton V.; Levichev, Sergey
Abstract: The effects of indium composition and the thickness of the combined InGaAs/GaAs thin cap layer on the energy spectra and relative electron–hole alignment of InAs quantum dots (QDs) grown by metal organic vapor phase epitaxy (MOVPE) are investigated by photoelectrical spectroscopy in a semiconductor/electrolyte system. In structures with InAs QDs and an InGaAs strain reducing layer, the shift of the hole׳s wave function to the QDs׳ top was revealed, which indicates In enrichment of the area near the top of QD׳. In structures with an ultrathin GaAs cap layer a change of the sign of the built-in dipole moment was observed. This is explained by coupling effects of quantum-confined electrons with surface states. Highlights: Stark effect studies on the InAs/GaAs quantum dots with ultrathin cap layers. Strong influence of the cap layer parameters on energy spectra and dipole moment. InGaAs strain reducing layer shifts the hole׳s wave function to the top of QDs. The sign of the ODs dipole moment changes in structures with cap layer <5 nm.